Weldability Investigation and Optimization of Process Variables for TIG-Welded Aluminium Alloy (AA 8006) - T. Sathish; S. Tharmalingam; V. Mohanavel; K. S. Ashraff Ali; Alagar Karthick; M. Ravichandran; Sivanraju Rajkumar (Advances in Materials Science and Engineering)
Aluminium and its alloys play a significant role in engineering material applications due to its low weight ratio and superior corrosion resistance. The welding of aluminium alloy is challenging for the normal conventional arc welding processes. This research tries to resolve those issues by the Tungsten Inert Gas welding process. The TIG welding method is an easy, friendly process to perform welding. The widely applicable wrought aluminium AA8006 alloy, which was not considered for TIG welding in earlier studies, is considered in this investigation. For optimizing the number of experiments, the Taguchi experimental design of L9 orthogonal array type experimental design/plan was employed by considering major influencing process parameters like welding speed, base current, and peak current at three levels. The welded samples are included to investigate mechanical characterizations like surface hardness and strengths for standing tensile and impact loading. The results of the investigation on mechanical characterization of permanent joint of aluminium AA8006 alloy TIG welding were statistically analyzed and discussed. The 3D profilometric images of tensile-tested specimens were investigated, and they suggested optimized process parameters based on the result investigations.